Crystallization and preliminary X-ray crystallographic studies of Mycobacterium tuberculosis chorismate mutase - Qamra, Rohini (International Union of Crystallography, 2005)
Chorismate mutase catalyzes the first committed step in the biosynthesis of the aromatic amino acids phenylalanine and tyrosine in bacteria, fungi and higher plants. The recent re-annotation of the Mycobacterium tuberculosis genome has revealed the presence of a duplicate set of genes coding for chorismate mutase. The mycobacterial gene Rv1885c bears <20% sequence homology to other bacterial chorismate mutases, thus serving as a potential target for the development of inhibitors specific to the pathogen. The M. tuberculosis chorismate mutase was crystallized in space group C2 and the crystals diffracted to a resolution of 2.2 Å. Matthews coefficient and self-rotation function calculations revealed the presence of two monomers in the asymmetric unit.